Critical Review on Plant Micropropagation of Ethiopian Plants Reported So Far: Existing Gaps, Required Standardization, and Future Research Direction - Genet Birmeta; Tura Safawo; Mulatu Geleta Dida; Endashaw Bekele (Advances in Agriculture)
Plant micropropagation research in Ethiopia requires concerted efforts to meet desired levels of application for sustainable utilization of the country's diverse plant genetic resources. The purpose of the present review is to provide an update on the results of plant micropropagation conducted so far in Ethiopia. It assessed their strengths and identified gaps in order to standardize research methods and indicate future research directions. Two cereals, three oil crops, three spices, five medicinal plants, two high-value crops, six fruit plants, nine root crops, and one endangered multipurpose shrub were reviewed. The assessment of previously published research was carried out in terms of methods used in the selection of ex plants and their disinfestations, culture vessels, and media used with a variety of combinations and concentrations of plant growth regulators, macro- and micronutrient requirements, culture environments, and genetic stability of regenerated plantlets. Further assessments include the utilization of plant growth-promoting microbes and applications of “omics” research in order to establish standardized, efficient, and cost-effective micropropagation techniques. The findings of the assessments are summarized and current advances are highlighted, along with recommendations for future plant micropropagation studies in the country.